Applied sports science and medicine for female cricket players: Systematic scoping review - Jacobs, J.; Brandt, C.; Grobler, N.; Saw, A.; Olivier, B. (Journal of Sports Sciences, 2025)
This review mapped currently available sports science and sports medicine (SSSM) research specific to female cricket players. Original research was included if data on female cricket players was presented, all ages and levels worldwide, from the earliest records to 19 January 2025. Databases searched included MEDLINE, SPORTDiscus, EBSCOhost, ProQuest Health, ScienceDirect, Medical Complete, and Scopus, along with trial registers and grey literature. The database search identified 13,795 studies, with an extra 104 added from citation tracking and other sources, with 179 studies that met the inclusion criteria. Eight SSSM themes were covered, including performance (n = 60), injury (n = 44), psychology (n = 38), health (n = 21), match characteristics (n = 6), anthropometry (n = 4), physiology (n = 4), and nutrition and hydration (n = 2). Gaps in the literature were identified for female-specific health (e.g. menstrual cycle, pregnancy), and several other domains, which currently have insufficient evidence. The synthesis of information in this review supports practitioners, whilst the identified gaps direct future research.